THE EFFECT OF SEA TRANSPORTATION, CONNECTIVITY AND GOVERNMENT POLICIES ON THE PEOPLE'S ECONOMY - H. Kamarul Hidayat, S.Pel,.MM.Tr; Prof. Dr. Muh Asdar, SE., MS.i; Prof. Dr. Ir. Jamaluddin Jompa, MS.c; Dr. Ir. L. Denny Siahaan, MS.Tr., APU (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This research was carried out with the aim of knowing and analyzing the effect of sea transportation, connectivity and government policies on the people's economy. The research method uses a mix method approach. The research population is the community around the outermost areas of Natuna Regency, Bunguran Island. The number of samples was determined based on the Slovin formula (Riduwan 2015) of 100 respondents. The method of determining the sampling using Non-Probability Sampling. The data analysis method used is the Structural Equation Model (SEM) approach using Smart PLS (Partial Least Square) 3.0. The results of the study show that sea transportation, connectivity and government policies have a significant effect on the people's economy on Bunguran Island, Natuna Regency